A rare case of odontogenic myxoma of maxilla - Shanmugam, Subbiah; Arumugam, Karthik (International Surgery Journal, 2024)
Odontogenic myxoma is a benign locally aggressive rare intraosseous neoplasm, originating from the odontogenic ectomesenchyme in second and third decades of life. Clinically they are slow growing, indolent, expansile, non-metastasizing involving predominantly mandible than maxilla. Maxillary odontogenic tumor spreads more aggressively through maxilla than mandible hence the need to address the tumor early and also the reconstruction of the maxillary defect following defect is uniquely challenging. This is a report of a rare case of left maxillary odontogenic myxoma which was locally aggressive and causing significant maxillary erosion in a 35 year old female, left subtotal maxillectomy done using Weber-Fergusson approach with Dieffenbach’s modification and the defect repaired with temporalis muscle flap.